The ICMI (Association of Indonesian Muslim Intellectuals) and Its Political Tendency during the Indonesian New Order - Imron Rosidi (Universitas Batanghari Jambi, 2022)
The Association of Indonesian Muslim Intellectuals (ICMI), which was founded on 7 December 1990, was an important and quite populist organization during the end of the New Order. This article aims to explain the political tendencies of ICMI in Islamic politics in Indonesia. This article uses a historical approach from available documents such as articles, books and others. This article finds that the establishment of ICMI in its development was used by its members as a political tool. Between the State (the New Order government) and ICMI have a mutually beneficial relationship. On the one hand, with the existence of ICMI, Muslim groups who are members of ICMI are easier to promote Islamic values to the State so that the State is expected to be more Islamic. On the other hand, the New Order State used ICMI as a political tool. The New Order embraced Muslim groups into ICMI to support the continuation of the New Order's political power.